The Readability of Sustainability Reporting in New Zealand over time - Azadeh Nilipour; Tracy-Anne De Silva; Xuedong Li (Australasian Accounting, Business and Finance Journal, 2020)
This paper examines the readability of sustainability reporting in the annual reports, and stand-alone reports of New Zealand listed companies over a ten-year period. Sustainability reporting was manually extracted from 264 reports, and readability software was used to identify the readability scores using five readability indices. Additionally, the effects of reporting quantity, environmental sensitivity, and global listing on the readability of sustainability reporting were examined. The results show that over the ten-year period readability has improved by only 6.5 per cent, despite a substantial increase in the number of companies reporting sustainability information, and an increase in the quantity of sustainability reporting from almost a third of the companies. This research also finds that there is a statistically significant negative correlation between the average readability score and reporting quantity; meaning longer sustainability reports have lower readability scores (i.e. they are more readable). The findings indicate that environmentally sensitive companies published more readable sustainability information in comparison to companies from non-environmentally sensitive industries. However, in terms of readability, there is no difference between the reports published by companies listed only on the New Zealand Stock Exchange (NZX) and the reports published by companies listed on multiple stock exchanges. This research is the first readability study examining sustainability reporting in New Zealand. It provides companies, users of sustainability information and regulators with knowledge of the readability of voluntary sustainability reporting, showing that little change has occurred over time. It suggests a strong possibility of obfuscation and thus, a risk that sustainability reporting is sending the wrong signal to stakeholders.
Keywords: Readability; Sustainability Reporting; Obfuscation; Quantity; Environmental Sensitivity; New Zealand Stock Exchange (NZX); Global Listing